The Influence of Local Cultural Values in the Traditional Music Learning Process in the Sendratasik Department - Armez Hidayat, Hengki; Syeilendra, Syeilendra; Marzam, Marzam; Hakim, Uswatul; Dhari, Belirda Wulan; Silahudin, Syafa’atussara (Gondang: Jurnal Seni dan Budaya, 2024)
Traditional music as an integral part of a society's cultural wealth has aesthetic value and plays a role in deepening cultural identity. However, in the era of globalization and modernization, traditional music is often threatened by changes in values and lifestyles that dominate from outside the culture. This article explores the influence of local cultural values on the traditional music education process in the Sendratasik Department. The main challenge is maintaining the existence of traditional music amidst the ever-changing interests of the younger generation. The research is a type of qualitative research with a case study approach. Through in-depth interviews, document analysis, and direct observation, this research aims to understand the extent to which local cultural values influence students' attitudes, interests, and participation in learning traditional music. The research results show that curriculum implementation through face-to-face lectures, online learning, lecturer collaboration, and integration of educational technology are effective strategies for maintaining the existence of traditional music. Analysis of the impact of globalization shows that traditional music needs to adapt to contemporary trends to remain relevant. Traditional music education also plays a role in developing student character, such as creativity, communication skills, empathy, pedagogical skills, discipline, collaboration, understanding of cultural diversity, understanding of technology, self-development, spirit of inclusivity, as well as creation and performance. This research is expected to contribute to the development of learning strategies and curricula that focus on maintaining and developing traditional music as an inseparable part of cultural heritage that is alive and relevant in today's society.